2019
DOI: 10.1177/0018720819858792
|View full text |Cite
|
Sign up to set email alerts
|

Effects of School Backpacks on Spine Biomechanics During Daily Activities: A Narrative Review of Literature

Abstract: Objective: The purpose of this narrative review is to summarize the effects of carrying school backpacks on spine and low-back biomechanics as a risk factor for low back pain in young individuals. Background: Backpacks constitute a considerable daily load for schoolchildren. Consistently, a large number of children attribute their low back pain experience to backpack use. Method: A literature search was conducted using a combination of keywords related to the impact of carrying backpacks on lower back biomecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
1
7
0
1
Order By: Relevance
“…According to results in this study, most parts of body showed good postural balance but some areas as trunk which showed fair postural balance, 46.2 % were fair and 10.3% were poor and 43.4 % good, these results indicating that heavy backpacks alter the mechanics of trunk curvature that's why scoliosis is very common in children. According to a study postural deviations and load on spine can be prevented by reducing weight of bag packs and the duration of wearing the bags [15]. Similar to the current study other studies finds that with variation in the weight of bags after one schooling year changes were found in the postures especially in parameters of rotation.…”
Section: Discussionsupporting
confidence: 87%
“…According to results in this study, most parts of body showed good postural balance but some areas as trunk which showed fair postural balance, 46.2 % were fair and 10.3% were poor and 43.4 % good, these results indicating that heavy backpacks alter the mechanics of trunk curvature that's why scoliosis is very common in children. According to a study postural deviations and load on spine can be prevented by reducing weight of bag packs and the duration of wearing the bags [15]. Similar to the current study other studies finds that with variation in the weight of bags after one schooling year changes were found in the postures especially in parameters of rotation.…”
Section: Discussionsupporting
confidence: 87%
“…Obwohl das Thema des Tragens eines Schulrucksacks seit langem von wissenschaftlichem Interesse ist und die Traglast biomechanische Anpassungen in RĂĽcken und Körperhaltung bewirkt [ 17 ], konnte eine Kausalität fĂĽr das Auftreten von RĂĽckenschmerzen bisher nicht eindeutig belegt werden [ 32 , 34 ].…”
Section: Hintergrundunclassified
“…The extra load caused by backpacks and the posture of carrying backpacks may cause considerable spine load. Moreover, the mechanical demand on the lower back caused by the trunk movement caused by backpacks increases, which needs to be balanced by active and passive responses of the lumbar tissue [28] .…”
Section: Resultsmentioning
confidence: 99%